DAMPAK KEBAKARAN HUTAN DAN LAHAN TERHADAP SEKTOR PERTANIAN DI KABUPATEN KAMPAR - Atanasius Bima Yudhana; Endah Purwaningsih (JURUSAN GEOGRAFI FIS UNP, 2021)
The research objectives are: 1) Determination of the distribution pattern of hotspots. 2) to know how much economic losses in the agricultural sector are caused by forest and land fires. The method used is Nearest Neighbor Analysis (NNA), which is used in Arcgis software to determine the distribution pattern of hotspots (hotspots) with a given index value, Total Economic Value (TEV) method with the production impact method approach . Based on the research results 1) the distribution pattern of hotspots (hotspots) in 2018 with a total of 59 points, the XII Koto Kampar district is a burn-prone area because there are 32 points with a ratio of 0.48, which means clustering. There were 148 points in 2019. Kampar Kiri Hilir district is a fire hazard area as there are 33 points with a ratio of 0.38 which means they are grouped. District XII Koto Kampar has the most hotspots for 2 years in a row, which means this area is prone to burns. 2) There are around 6,518.05 hectares of burned land in the oil palm plantations. The loss is estimated at Rp. 5.70 billion in 2018 and Rp. 111.98 billion in 2019.